An airblast hazard simulation engine for block caving sites. (July 2018) - Galindo-Torres, S.A.; Palma, S.; Quintero, S.; Scheuermann, A.; Zhang, X.; Krabbenhoft, K.; Ruest, M.; Finn, D.
Abstract: In this paper, a weakly compressible Lattice Boltzmann code is coupled with a realistic shape Discrete Element algorithm to create a simulation software to estimate the airspeed happening at airblast events in three dimensions. In an airblast event, air is compressed between falling rocks and the muckpile when the block caving method is used, creating potential hazardous air gusts compromising the safety of personnel and equipment. This work shows how the coupled code is capable of reproducing the key physical layers involved in this phenomenon such as the airspeeds attained by falling bodies in funnel geometries. After some validation examples, the code is used to evaluate the effect of the underground mine geometrical parameters on the potential airspeed. These examples show the potential of the software to be used by mining engineers to estimate accurately the impact of an airblast event.